Reformulating the Concept of Nusyuz in Malaysian Islamic Family Law: A Mubadalah-Based Gender Justice Analysis in Malaysian Islamic Family Law - Wan Abdul Rahim Bin Wan Abd Aziz; Achmad Faishal (Journal of Islamic Mubadalah, 2025)
This article reexamines the legal construction of nusyuz within Malaysian Islamic Family Law. The formulation that positions obedience as a unilateral obligation of the wife generates serious concerns related to gender hierarchy and directly affects women’s rights to maintenance, protection, dignity, and access to justice. The study aims to evaluate gender bias in both the legal definition and judicial application of nusyuz, while proposing an alternative framework based on the Mubadalah hermeneutical theory, which emphasizes reciprocity, shared responsibility, and egalitarian family relations. This study employs a qualitative normative legal method with a comparative approach to examine Islamic family law enactments across several states in Malaysia, analyzed through the framework of the theory of mubādalah. The novelty of this research lies in the application of the mubādalah perspective as an analytical framework to articulate principles of reciprocity and justice in Islamic family law. The research results found that reduction of nusyuz into a one-sided duty imposed on women not only reinforces unequal power relations but also undermines legal protection for women in situations of domestic conflict. Through the Mubadalah perspective, this article proposes the reformulation of nusyuz as a bilateral legal category grounded in moral and legal reciprocity. Recommendations include legislative revision, the development of more equitable judicial guidelines, and the integration of reciprocal principles into future reforms of Malaysian Islamic family law.